2022
DOI: 10.1002/arch.21996
|View full text |Cite
|
Sign up to set email alerts
|

Current understandings of olfactory molecular events in the Asian corn borer, Ostrinia furnacalis (Lepidoptera: Crambidae)

Abstract: The Asian corn borer Ostrinia furnacalis (Lepidoptera: Crambidae) is a serious corn pest with widespread distribution in East Asia. Its olfactory mechanism is a focus of scientific study, aiming to find good ways to control this pest. Molecular events are considered to be important in olfactory mechanism. Current understandings of olfactory molecular events in O. furnacalis, mainly involving sex pheromones and olfactory proteins, were summarized to provide a reference for further studies. O. furnacalis sex phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…Both the qRT-PCR results and FPKM values indicated that EsigOR16 exhibits the highest expression among the odorant receptors, making it the key receptor involved in odorant recognition. Likely, in O. furnacalis, OfurOR8, OfurOR7, and OfurOR5b primarily respond to the sex pheromone components of other Ostrinia species, while OfurOR27 strongly responds to plant odorants such as nonanal, octanal, and 1-octanol [9]. These findings highlight the specificity and diversity of odorant receptors in different insect species, reflecting the species' adaptations to specific ecological niches and behaviors.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Both the qRT-PCR results and FPKM values indicated that EsigOR16 exhibits the highest expression among the odorant receptors, making it the key receptor involved in odorant recognition. Likely, in O. furnacalis, OfurOR8, OfurOR7, and OfurOR5b primarily respond to the sex pheromone components of other Ostrinia species, while OfurOR27 strongly responds to plant odorants such as nonanal, octanal, and 1-octanol [9]. These findings highlight the specificity and diversity of odorant receptors in different insect species, reflecting the species' adaptations to specific ecological niches and behaviors.…”
Section: Discussionmentioning
confidence: 72%
“…Specifically, the sex pheromones E-12-tetradecenyl acetate and Z-12-tetradecenyl acetate are recognized and bound by the pheromone-binding proteins (PBPs) OfurPBP3 and OfurPBP2. Subsequently, these bound pheromones are transported to the odorant receptors (ORs) OfurOR4 and OfurOR6, leading to their activation [9]. Factually, ORs function as the primary receptors, and they form heteromers with a shared, highly conserved subunit known as the OR coreceptor (Orco) in insects [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…He et al sequenced the antennal transcriptome of P. operculella and analyzed the function of the sex pheromone receptor PR in P. operculella [ 27 ]. Li et al analyzed the types and functions of odorant-binding proteins (OBPs) in P. operculella , providing important insights for the study of the chemical ecology of P. operculella [ 28 ] . To further investigate the chemical ecological mechanisms of P. operculella and P. absoluta , comprehensive identification and analysis of their chemosensory genes are urgently needed and potentially of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…Olfaction plays an essential role in the regulation of a diverse array of physiological behaviors throughout the life cycles of insects, such as foraging, predator avoidance, mating, and oviposition (Suh et al, 2014). The processes that facilitate olfactory perception involve interactions between odor molecules and various families of olfactory proteins, including odorant‐binding proteins (OBPs), chemosensory proteins (CSPs), olfactory receptors, ionotropic receptors, and sensory neuron membrane proteins (Leal, 2013; Li & Zhang, 2022). When hydrophobic odorant molecules (e.g., insect pheromones or host plant volatiles) penetrate the cuticle pores at the surface of antennal sensilla, they are proposed to be trapped and bound to OBPs and CSPs.…”
Section: Introductionmentioning
confidence: 99%
“…This is then followed by transport through the hydrophilic sensillum lymph towards the dendrites of olfactory receptor neurons. In turn, these bound molecules are then detected by chemosensory receptors of olfactory receptor neurons, which triggers the propagation of electrophysiological signals (Leal, 2013; Li & Zhang, 2022).…”
Section: Introductionmentioning
confidence: 99%